The temple of my familiar : a novel - Walker, Alice, 1944- (Amistad, an imprint of HarperCollinsPublishers, 2023)
"Celie and Shug from The Color Purple subtly shadow the lives of the dozens of astonishing characters in The Temple of My Familiar, all of whom are dealing in some way with the legacy of the African experience in America. From recent African immigrants to a woman who grew up in the mixed-race rainforest communities of South America to Celie's own granddaughter living in modern-day San Francisco, they must come to terms with the brutal stories of their ancestors in order to confront their own troubled lives. Described by the author as 'a romance of the last 500,000 years,' The Temple of My Familiar creates a new mythology from old fables and history, and along with it a profoundly spiritual explanation for centuries of shared African American experience." --